Rhododendron wumengense sp. nov. (Ericaceae) from northeast Yunnan, China - Zhao, Yong-Li; Yi, Xiang-Bo; Hao, Yong-Song; Chen, Ting; Ma, Yong-Peng; Liu, De-Tuan (Phytotaxa, 2025)
Rhododendron wumengense (Ericaceae), a new species discovered in Zhaotong City in northeast Yunnan Province, China, is described and illustrated. Morphologically, the new species is most similar to R. orbiculare and R. williamsianum. However, it can easily be distinguished from R. orbiculare by its densely glandular young shoots, non-overlapping leaf base lobes, yellowish corolla, and straight, 7–8-locular capsule. It can also be easily distinguished from R. williamsianum in its young shoots densely covered with short-stalked glands, yellowish corolla, more flowers per inflorescence, a 7–8-locular capsule and a glabrous style. Based on the IUCN Red List categories and criteria, R. wumengense is assessed as Critically Endangered.